Pengaruh Latihan Fartlek terhadap Peningkatan Vo2max Atlet Pencak Silat Tapak Suci - Taupik Akbar; Zihan Novita Sari; Ardo Okilanda; Qorry Armen Gemael (Jurnal Patriot, 2021)
This study aims to determine how much influence Fartlek training has on the VO2Max results of Baturaja pencak silat athletes and to compile an interesting and fun training program. In this study, the population was 60 male athletes of pencak silat Baturaja. The number of samples of this study was 60 male athletes using random sampling techniques and divided by ordinal pairing techniques into 30 athletes as the experimental class and 30 athletes as the control class. The experimental class was given Fartlek practice and the control class was not given treatment. The data collection technique used the preliminary test and the final test. The statistics used to analyze the data in the hypothetical research with the t-test statistic, the results show that tcount = 42.559> ttable = 1.771. Thus, fartlek training has an effect on increasing VO2Max for male athletes in pencak silat t.apak Suci Baturaja